Factors influencing starch digestibility - Noda, Takahiro; Sarker, Md. Zaidul Islam (2012)
Starch that avoids digestion by amylases in the small intestine and passes to the large bowel for fermentation is defined as resistant starch (RS). RS appears to be desirable in human health, as it has functional properties similar to fermentable dietary fibers. The amount of RS is related to the rate of starch digestion by amylases. Enzymatic digestibility of starch is largely dependent on physicochemical properties of the starch. Enzymatic digestibility of gelatinized and raw starch is an important property in food manufacture. In potato starch, raw starch granules have larger granule size, which is highly resistant to hydrolysis by amylase. In addition, potato starch has a definitely higher amount of covalently bound phosphate compared to other starches. In this study, enzymatic digestibility of raw and gelatinized starches in various potato starches besides sweet potato, cassava and yam starches were determined along with other starch properties, median granule size, phosphorus content, and pasting properties. Furthermore, the correlation coefficients were calculated between the enzymatic digestibility and other starch quality parameters. A larger granule size was closely associated with a lower digestibility in raw starch, while the digestibility in gelatinized starch did not correlate with the median granule size. An increase in the phosphorus content resulted in a definitely lower digestibility in raw starch and tended to decrease the digestibility in gelatinized starch for the composite of potato and other starches.